Propranolol can correct prolonged QT intervals in patients with cirrhosis - Han, Huanqin; Chen, Junlian; Deng, Zhirong; Li, Tingting; Qi, Xiaoying; Deng, Wei; Wu, Zunge; Xiao, Chuli; Zheng, Weiqiang; Du, Yujun (Frontiers in Pharmacology, 2024)
Background: Prolongation of the QT interval is extremely common in patients with cirrhosis and affects their outcomes. Propranolol is often used for the prevention of gastroesophageal variceal hemorrhage in patients with cirrhosis; however, it remains uncertain whether it exerts a corrective effect on QT interval prolongation in patients with cirrhosis. Methods: A retrospective cohort study approach was adopted. Patients with cirrhosis complicated by moderate to severe gastroesophageal varices were included. Patients were divided into the propranolol and control groups based on whether they had received propranolol. Upon hospital admission, patients underwent testing of liver and kidney function, electrolytes, and coagulation function, as well as abdominal ultrasonography and electrocardiography. In addition to conventional treatment, patients were followed up after the use or non-use of propranolol for treatment and subsequently underwent reexamination of the items mentioned above. Results: The propranolol group (26 patients) had a baseline corrected QT (QTc) interval of 450.23 ± 37.18 ms; 14 patients (53.8%) exhibited QTc interval prolongation. Follow-up was continued for a median duration of 7.00 days after the administration of propranolol and conventional treatment. Electrocardiography reexamination revealed a decrease in the QTc interval to 431.04 ± 34.64 ms (P=0.014), and the number of patients with QTc interval prolongation decreased to five (19.2%; P<0.001). After treatment with propranolol and multimodal therapy, normalization of the QTc interval occurred in nine patients with QTc interval prolongation, leading to a normalization rate of 64.3% (9/14). The control group (n=58) had a baseline QTc interval of 453.74 ± 30.03 ms, and 33 patients (56.9%) exhibited QTc interval prolongation. After follow-up for a median duration of 7.50 days, the QTc interval was 451.79 ± 34.56 ms (P=0.482), and the number of patients with QTc interval prolongation decreased to 30 (51.7%; P=0.457). The QTc interval normalization rate of patients with QTc interval prolongation was merely 10.0% (3/33), which was significantly lower than that of the propranolol group (P<0.001). Conclusion: In patients with cirrhosis complicated by QT interval prolongation, the short-term use of propranolol aids in the correction of a long QT interval and provides positive therapeutic value for cirrhotic cardiomyopathy.